The importance of plant cover and predation in shaping a desert community. (December 2016) - Segoli, Moran; Groner, Elli; Ayal, Yoram
Abstract: The classical paradigm describe desert communities as being controlled by abiotic conditions and therefore it was assumed that predation had a limited role in the determination of desert community structure and that only one effective trophic level was expected. In the Negev desert, the desert isopod ( Hemilepistus raeumuri ) is common in the less productive habitats but almost absent from the more productive wadis. In the present study we tested whether predation by ectothermic predators has a role in controlling isopod populations in wadis. We hypothesized that plant cover provides a refuge for these predators from secondary endothermic predators. We addressed this hypothesis by comparing isopod survivorship with and without predation exclusion, and with and without plant cover removal. Isopods protected from predation had a sustainable population whereas unprotected isopods had an unsustainable sink population. Removal of plant cover did not affect the survivorship of predator-protected isopods, however it did increase the survivorship and reduced predation pressure when not protected from predators, for at least four years. Hence, we conclude that predation controls isopod population and causes an unsustainable sink population in wadis. We have shown that plant cover mediates predation and that some habitats in the desert have an effective third trophic level, suggesting that energy is not the major limiting factor in determining the length of food chains. Highlights: Plant cover mediates predation in deserts. Plant cover provides a refuge for primary ectothermic predators from secondary endothermic predators. Desert can have an effective third trophic level.